B-GATA transcription factors – insights into their structure, regulation, and role in plant development - Behringer, Carina; Schwechheimer, Claus (Frontiers in Plant Science, 2015)
GATA transcription factors are evolutionarily conserved transcriptional regulators that recognize promoter elements with a G-A-T-A core sequence. In comparison to animal genomes, the GATA transcription factor family in plants is comparatively large with approximately 30 members. In spite of a long-standing interest of plant molecular biologists in GATA factors, only research conducted in the last years has led to reliable insights into their functions during plant development. Here, we review the current knowledge on B-GATAs, one of four GATA factor subfamilies from Arabidopsis thaliana. We show that B-GATAs can be subdivided based on structural features and their biological function into family members with a C-terminal LLM- (leucine-leucine-methionine) domain or an N-terminal HAN- (HANABA TARANU) domain. The paralogous GNC (GATA, NITRATE-INDUCIBLE, CARBON-METABOLISM INVOLVED) and CGA1/GNL (CYTOKININ-INDUCED GATA1/GNC-LIKE) are introduced as LLM-domain containing B-GATAs from Arabidopsis that control germination, greening, senescence and flowering time downstream from several growth regulatory signals including light and the hormones gibberellin, auxin, and cytokinin. Arabidopsis HAN and its monocot-specific paralogs from rice (NECK LEAF1), maize (TASSEL SHEATH1), and barley (THIRD OUTER GLUME) are HAN-domain-containing B-GATAs with a predominant role in embryo development and floral development. We also review GATA23, a regulator of lateral root initiation from Arabidopsis, that is closely related to GNC and GNL but has a degenerate LLM-domain that is seemingly specific for the Brassicaceae family. The Brassicaceae-specific GATA23 together with the above-mentioned monocot-specific HAN-domain GATAs provide evidence that neofunctionalization of the B-GATAs was used during plant evolution to expand the functional repertoire of these transcription factors.